Digital transformation, innovation and economic performance : a comparative study of Finland and India - Chitnis, Aditi (2018)
Transformations in the information and communication technologies has had a profound effect on innovation and in turn the economic growth within countries. These changes have already been reflected in the corporate environment by improved market mobility and compounding profitability of corporations. These quantum leaps have been well drafted in literature studies and various other international reports. However, the standpoint of the government at the national level and their approaches to facilitate these digital innovations has been subjected to limited research. Thus, this study primarily aims to shed light on what approaches have been taken by the governments and how have these approaches evolved so as to integrate and facilitate digital transformation and innovation to drive economic growth within the country. This study takes a comparative approach by comparing innovation policies in a developed country, in this case Finland, and a developing country, India, for a period of 15 years from 2002 until 2017. The research literature builds on the national innovation systems framework to guide this study. Secondary data in the form of official government reports from both countries was made use of. In particular 22 reports from Finland and 16 reports from India were analyzed. The results show a detailed view of the various actors involved in forming the national innovation system in both countries. Furthermore, they also showcase the different ways in which the policy makers have responded to technological and economic changes, the various programs initiated by them in order to empower the citizens, businesses and research institutions. Interestingly, both Finland and India at certain time periods can be seen to cope with similar challenges and both portray incremental and radical changes; the only difference being in their ability to firmly implement these changes. Eventually, the findings also suggest that both of these countries still need to work hard to better exploit their inherent capabilities to stay competent and competitive.